Repurposing of Metformin for the prevention and treatment of Tuberculosis - Navya Vyas; Rakhi Punchathidil; Ansuman Swain; Irfan Shakeer; Badikol Shrikar Reddy; Mohan Kamalanivas Manu; Sonal Sekhar Miraj (Universidade de São Paulo, 2022)
Abstract The bidirectional relationship between tuberculosis (TB) and diabetes mellitus (DM) is a major concern for medical professionals and epidemiologists as DM affects the severity, progress and outcome of TB and vice versa. Patients affected with TB have a higher rate of morbidity, treatment failure and mortality. Likewise, DM triples the risk of contracting TB and therefore poses a threat to the progress made in the reduction of TB incidence. Hence, it is pivotal to address both the diseases keeping in mind the each other. It is known that adjunct therapy with immunomodulatory drugs can enhance TB immunity among diabetic patients. Metformin, a commonly used anti-diabetic drug with adenosine monophosphate-activated protein kinase (AMPK) activation property, has shown the capacity to reduce the growth of Mycobacterium tuberculosis within the cell. This drug inhibits the mitochondrial complex and possesses anti-inflammatory action. Therefore, Metformin can be considered as an ideal molecule for host-directed or host-targeted therapy for TB.